Ubiquitous Environments and Brazilian Personas: Can our citizens universally access this technology? - Alencar, Tatiana Silva de; Neris, Vânia Paula de Almeida (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2012: Anais do XXXIX Seminário Integrado de Software e Hardware, 2012)
Ubiquitous technology has great power to simplify and improve people’s life. However, as the 4th Grand Research Challenge for the Brazilian Computer Society mentions, it is necessary to extend computational systems to all Brazilians, respecting their diversity and differences. This paper presents an analytical approach to evaluate ubiquitous environments which considers the Personas technique as well as videos, scenarios and the GQM (Goal, Question and Metric) method. A feasibility study in the Brazilian scenario reveals that known ubiquitous environments partially meet the interaction requirements of disable people.